Endometrial cancer of the very elderly: Management and survival in the Francogyn population. Issue 5 (May 2023) - Martin, Flore-Anne; Dion, Ludivine; Nyangoh Timoh, Krystel; Dupré, Pierre François; Azaïs, Henri; Bendifallah, Sofiane; Touboul, Cyril; Dabi, Yohann; Graesslin, Olivier; Raimond, Emilie; Costaz, Hélène; Kerbage, Yohan; et al.
Abstract: Introduction: We aimed to describe management and survival of patients with endometrial cancer (EC) ≥80 years to identify poor prognosis criteria. Methods: We collected clinical, histologic, surgical and follow-up data for patients with EC ≥ 80 years included in a multicenter French cohort (FRANCOGYN) who underwent primary surgical treatment from 1999 to 2019. The outcomes were overall survival (OS) and disease-free survival (DFS). We performed a descriptive analysis then a survival time analysis and comparison using the Kaplan Meier method and log-rank test. Results: Of the 1647 patients with EC who received treatment during the study period, 184 (11.17%) were ≥80 years. The mean age was 84 years (±3.34). Thirty-three patients (25.4%) died during the follow-up period and 26 relapsed (18.4%). Forty-nine patients were lost to follow-up (27.37%). The median follow-up time was 15.3 months (4.9–28.8). The median OS and DFS was 16.4 months (6.3–24.9) and 13.6 months (4.5–26.6), respectively. Eighty-three patients received adjuvant therapy (45.11%), out of 95 who had a formal or relative indication. Four patients received adjuvant chemotherapy (2.6%), out of 61 who had a formal or relative indication. Inappropriate or underuse of chemotherapy was significantly associated with a lower median OS of 12.6 months [3.73–24] versus 17.3 months [7.93–41.77] when performed appropriately (HR = 4.14, CI 95% [1.62–10.56]), and a lower median DFS of 10.83 months [3.73–24] versus 17.3 months [7.93–28.5] (HR = 9.04, CI 95% [2.04–40.12]). Conclusion: Our results suggest that very elderly patients with EC should receive adjuvant chemotherapy according to the standard care guidelines.